Efectos de la digestibilidad in vitro de la panca de arroz amonificada con urea como suplemento alimenticio en vacas lecheras del cantón Baba, Los Ríos - Cedeño Rojas, Manuel Antonio (2020)
This investigation was carried out at Hacienda La Delia, located in the Baba canton of the Los Ríos province. The objective of this research was to evaluate the in vitro digestibility of rice panca treated with urea. Unammonified rice pan 1kg, polyethylene bags and gramera scale were used. A completely randomized design with a 2x3 bifactorial arrangement was used for this study. The 5% Tukey test was used for the evaluation of means. The in vitro digestibility of rice panca treated with urea and without urea was evaluated. Applying the Tukey mean comparison method to 5%, it was possible to verify that there was a difference between the means of the treatments. The results obtained were: in the first factor, the ammonified rice pan reached an average of 48.84%. In the second factor, the stem fraction reached the best average with 48.31%. In the interaction, the best treatment was the ammonified pan with stem fraction with 52.96% and the lowest value is recorded by the unammonified rice pan with leaf fraction with an in vitro digestibility of 38.88%. In the first factor, the ammoniated rice pan reached an average of 48.25%. In the second factor, the stem fraction reached the best average with 47.38%. In the interaction, the best treatment was the ammonified pan with stem fraction with 51.51%. Once the analyzes had been carried out, it was determined that the ammonified pan has higher digestibility than the unammonified pan, and the best results are located in the first period.